Peningkatan Pengetahuan dan Self-Efficacy Kader Posyandu dalam Melakukan Edukasi dan Pembuatan Media Edukasi Gizi - Siti Rahayu Nadhiroh; Trias Mahmudiono; Ira Suarilah; Ernadila Diasmarani Hargiyanto; Callista Naurah Azzahra; Sasha Anggita Ramadhan; Soraya Tri Widayani; Eka Anisah Yusryana (Media Gizi Kesmas, 2024)
Backgroud: Kangean Island is one of the islands in Sumenep Regency, Madura, East Java. Malnutrition in under-five children is still one of the main problems in the Kangean Islands. In this regard, empowering posyandu (integrated service post) cadres to carry out nutrition education independently is one of the important factors in the success of reducing this nutritional problem. Objective: This paper analyzes the effectiveness of training activities to increase the knowledge and self-efficacy of posyandu cadres on Kangean Island, Sumenep Regency. Methods: Community service was carried out on Kangean Island on July 19 and 20, 2024 in the form of two activities, namely posyandu cadre training on how to carry out nutrition education and create good nutrition education media on the first day, and the second day was a nutrition education competition jamboree. Participants were 18 posyandu cadres from four villages on Kangean Island. The activity's success was evaluated using pre- and post-test questionnaire instruments and a paired sample t-test was carried out to see the difference in the average level of knowledge and self-efficacy before and after training. In addition, from the jamboree, it can be seen to what extent the cadres can implement the training materials. Results: The average score of knowledge and self-efficacy increased after the cadre training. There was a significant difference between the pre- and post-test for the cadres' self-efficacy level in providing education and making nutritional education media (p-value 0.024). In addition, each group from each posyandu representative succeeded in becoming educators and was able to make creative nutritional education media during the cadre jamboree. Conclusion: Community service in the form of training can increase the knowledge and self-efficacy of cadres in providing nutritional education and making nutritional education media. It is hoped that cadre training to provide nutritional education and make educational media can be carried out periodically by various related institutions. Some awards can also be held to increase the enthusiasm of cadres to carry out their duties.